Intergenerational power gap and R&D investment: Evidence from China - Yong Zhao; Xi Yang; Daqi Xin; Wencang Zhou; Shuaijun Zhang; Liying Wang (Journal of Innovation & Knowledge (JIK), 2023)
Family firms face the dual challenge of succession and innovation. Based on the attention-based view, this study empirically investigates the effect of intergenerational power gap on corporate R&D investment, using a sample of Chinese listed family firms. We find that intergenerational power gap has a negative effect on corporate R&D investment, and this negative relationship is amplified in traditional industries and in firms with a low proportion of institutional ownership. Our findings have theoretical and practical implications for R&D investment in the family business succession process.
Keywords: G30; G32; O32; 650; Family firms; Intergenerational power gap; R&D investment